Analysis and Research on Pollution Treatment Technology in Environmental Protection. Issue 4 (February 2020) - Liang, Xiaotian
Abstract: With the rapid development of the economy, the industrialization process has brought about a rapid improvement in people's quality of life, but it has caused pollution in the natural environment on which we depend. In order to protect the environment, the government has issued a number of policies and achieved great results. Based on this, this paper analyzes the status of environmental pollution in detail, and focuses on the analysis of CCAS process and SPR wastewater treatment technology, clarifies the importance of advanced pollution treatment technology to environmental protection, and proposes targeted strategic recommendations to promote Better and more sustainable development of the environment.